PENGARUH PEMBERIAN JUS SEMANGKA KUNING (Citrullus lanatus) TERHADAP KELELAHAN OTOT ANAEROBIK PADA ATLET SEPAKBOLA - Alamanda Devi Maharani; Ana Yuliah Rahmawati; Enik Sulistyowati; Setyo Prihatin (Poltekkes Kemenkes Semarang, 2019)
Background: Muscle fatigue in anaerobic activity occured, when athletes have high intensity activities. The accumulation of lactic acid in muscle and blood could inhibit muscle contraction caused low concentration and performance. Sitrulin in yellow watermelon (Citrullus lanatus) juice can delay muscle fatigue in anaerobic activity.Objective: To know the effect of Yellow Watermelon Juice (Citrullus lanatus) To Anaerobic Muscle Fatigue Index Athletes.Methods: This study used quasi experimental design with a pre-post test design group control design. The fourteen athletes who were randomly divided into control groups and treatment groups. The control group was given a placebo and the treatment group was given a 500 ml watermelon juice with a dose of 1,8gr of sitrulin during seven days. Yellow watermelon (Citrullus lanatus) juice are given 60 minutes before the test done. Anaerobic muscle fatigue in soccer athletes were measured using a RAST (Running-based Anaerobic Sprint Test) by calculating the Muscle Fatigue Index. Data were analyzed by Independent t-test.Results: In this study there was an increase category of muscle fatigue index from good category (0.21-3.31) to very good category (0.21), although both control and treatment group not significant different statistically (p = 0,532). The mean initial muscle fatigue index of the treatment and control group respectively (0.1157 ± 0.05) and (0.1486 ± 0.65). The mean final muscle fatigue index of the treatment and control group respectively (0.1229 ± 0.04) and (0.1371 ± 0.03).Conclusion:The adduction of yellow watermelon juice (citrullus lanatus) during seven days did not affect the reduction of anaerobic muscle fatigue (p = 0,532).